Optimalisasi Strategi Responsibilitas dalam Rantai Pasok pada CV. XYZ Furnitur untuk Meningkatkan Kepuasan Pelanggan - Feby Dendra; Agnes Vicky; Febriza Imansuri (Jurnal Industri dan Teknologi Samawa, 2025)
CV. XYZ Furniture, a company engaged in the rattan furniture industry in West Sumatra. This research aims to evaluate production strategies. Currently, the company implements an efficiency strategy by producing a constant number of guest chairs every period. However, this strategy poses problems in meeting customer demand during a spike, resulting in potential customer loss. This research explores changing strategies towards responsiveness as a solution to increase flexibility and meet customer needs more optimally. The methodology used is a case study through supply chain analysis, especially in the aspects of production, inventory, and logistics. The results of the study show that the implementation of a responsive strategy is able to increase customer satisfaction and improve supply chain performance, although it requires more careful cost management to overcome potential overtime costs and inventory. To overcome this, CV. XYZ Furniture needs to implement a Just-In-Time (JIT) or Pull System, as well as utilize information technology to improve supply chain communication. With a more responsive strategy, companies can improve competitiveness and profitability in the rattan furniture industry